IMPROVING LEARNING OUTCOMES USING MAKE A MATCH METHOD IN FIFTH GRADE STUDENTS AT SDN 020 NORTH SAMARINDA - Nur Agus Salim; Siska Oktaviani; Tria Yuliani (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2020)
This study intended to improve learning outcomes of events in life themes using make a match method for fifth grade students at SDN 020 Samarinda Utara in 2018/2019 academic year. The type of research used is CAR that is carried out in II cycles and each cycle consists of 3 meetings. The results showed that (1) The application of the make a match method in learning can increase the activities of teachers and students. The results reveal from the observations of teacher activity in the first cycle scored 58.8 to 78.8 in the second cycle. It was also proved by the results which getting a value of 60 in cycle I, increasing in cycle II with a value of 86.6. (2) The learning outcomes on theme 7 of the social studies subject matter have increased after taking action. It can be seen from the average class in the first cycle of 71.33 with a percentage of completeness that is 33.3%, in the second cycle to 80.83 with a percentage of completeness of 83.3%. (3) students' skills in making mind maps increased in cycle I gained an average value of 68.8, p and in cycle II scored 80.2.